2013
DOI: 10.1007/s10995-013-1311-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Recurrent Preterm Birth: Role of the Neonatal Follow-up Program

Abstract: OBJECTIVES Preterm birth (PTB) is a public health crisis in need of effective preventative strategies. Multi-disciplinary Neonatal Follow-up Programs (NFPs) provide health services to preterm infants at high risk for developmental problems after discharge from U.S. newborn intensive care units (NICUs). We aimed to determine whether NFPs are a potential effective venue for specialized maternal counseling and intervention aimed at reducing the high rate of recurrent PTB in this population. METHODS This prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The main mechanisms that have been suggested are inflammation, infection, and vascular pathologies [ 29 , 30 ]. Usually multiple etiologies are involved, including: cervical insufficiency, decline in progesterone action and insufficiency or ischemic placental−uterine unit [ 29 , 31 , 32 ]. Impaired placental implantation processes and insufficient fetal nutrition and growth may cause deliveries of SGA newborns, preeclampsia, perinatal mortality, placental abruption and PTD [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main mechanisms that have been suggested are inflammation, infection, and vascular pathologies [ 29 , 30 ]. Usually multiple etiologies are involved, including: cervical insufficiency, decline in progesterone action and insufficiency or ischemic placental−uterine unit [ 29 , 31 , 32 ]. Impaired placental implantation processes and insufficient fetal nutrition and growth may cause deliveries of SGA newborns, preeclampsia, perinatal mortality, placental abruption and PTD [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in mothers with premature neonates in the NICU showed that a small percentage of women were aware of the major risk factors for recurrent preterm birth and had a lower uptake of effective contraception. 11 , 12 Another study reported disparities in postpartum contraceptive counseling and effective contraceptive uptake in women with preterm infants. 38 Since this is a high-risk group for repeat preterm deliveries, there should be a focus on their reproductive plans and perceptions about contraception.…”
Section: Discussionmentioning
confidence: 99%
“…We also wanted to learn about the contraceptive choices of women with infants in the neonatal intensive care unit (NICU) since low use of effective contraception in women with preterm infants puts them at high risk for unintended pregnancy and recurrent preterm birth. 11 , 12 To our knowledge, there are few studies looking specifically at postpartum contraceptive choices of these women.…”
Section: Introductionmentioning
confidence: 99%
“…Most women are not aware of their own level of risk for PTB, and risky behaviors may continue as a result of inadequate knowledge. 33 Based on screening assessments, we should provide each patient with her own personal risk for PTB and engage her as a proactive partner in preventing PTB. 9 With better awareness of risk, physicians and patients are in a better position to target optimal weight management, and to tackle smoking cessation and avoidance of drugs and alcohol.…”
Section: Awarenessmentioning
confidence: 99%